A non-seminomatous extra-gonadal germ cell tumor responding to intensive treatment a case report - Harada, Akinori (Hinyokika kiyo. Acta urologica Japonica, 2006)
A 23-year-old man presented with lumbago as a chief complaint. Computed tomographic (CT) scan revealed multiple lung tumors, multiple liver tumors, bulky retroperitoneal tumors with marked elevation of serum lactic dehydrogenase (LDH), alpha-fetoprotein, and beta subunit of human chorionic gonadotropin (HCG-beta). The patient was referred to our hospital for treatment. Scrotal ultrasonography and physical examination revealed bilateral normal testes. Because of bulky retroperitoneal masses with elevated specific tumor markers as well as bilateral normal testes, our diagnosis led to extra-gonadal germ cell tumor. Because the pulmonary lesion had increased rapidly, chemotherapy was performed without the tumor biopsy. After multiple chemotherapy regimens including BEP (bleomycin, etoposide, cisplatin), high-dose chemotherapy, and TIN (paclitaxel, ifosfamide, nedaplatin), all tumor marker levels fell into within the normal range. The tumor size was decreased remarkably on CT. Then, retroperitoneal lymphadenectomy were performed to confirm whether they still contained viable tumor cells. They contained only necrotic tissues without viable cancer cells by pathological examination. Consequently, the patient has been free of recurrence for 18 months after intensive treatment